An assessment continuum: How healthcare professionals define and determine practice readiness of newly graduated registered nurses. Issue 2 (April 2020) - Harrison, Helena; Birks, Melanie; Franklin, Richard; Mills, Jane
Abstract: Background: Healthcare services require graduate nurses to be practice ready, however growing evidence implies that this is not the case. There is a lack of clarity in the literature around the concept of practice readiness and how this is determined. Without a clear definition to guide assessment processes, decisions about graduate nurse practice readiness will remain poorly defined and graduate nurses inadequately supported. Aim: As part of a larger body of work, this paper reports on how healthcare providers in one state in Australia define and determine graduate nurse practice readiness. Methods: This study employed an instrumental collective case study design using multiple methods of data collection and grounded theory methods of data analysis. Sixty-seven healthcare professionals located in four sites in one state in Australia participated. Findings: This study found that practice readiness is a multidimensional concept encompassing overlapping personal, clinical, industry and professional capabilities. These capabilities held true for participants in all contexts of practice. Practice readiness is assessed across a continuum as the graduate makes the transition from student to registered nurse. Graduates' level of confidence was found to be a critical factor in both demonstrating and determining practice readiness. Discussion: Decisions about graduate nurse practice readiness are largely subjective. An agreed understanding of practice readiness is required to ensure assessments and decisions about practice readiness are reliable and consistent and support the needs of graduate nurses and healthcare providers. Conclusion: A graduate nurse's first year of practice is an extension of their learning and development to become a competent registered nurse. Graduate nurses require experience as a registered nurse to be practice ready and achieve the necessary confidence and required competence for safe practice. In the current model of nurse education, meeting this need is difficult.